Juridical Analysis of Farmer Group Legal Security - Sulistio (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2023)
Farmers have made a real contribution to agricultural development and rural economic development. to realize food sovereignty, “food self-sufficiency and food security in a sustainable manner, farmers as actors of agricultural development need to be given protection”. The idea of forming a group comes from the fact that each individual cannot fulfil their needs individually as experienced by the less fortunate Panoramic farmer groups so they need support to develop their socio-economic life. The research was conducted as an effort to prove that the counselling activities provided were able to encourage the group. This study uses a legal sociology approach. This research took place in Pamotan Village, Dampit District, Malang Regency. Primary data was obtained from observation and direct interviews with informants and data analysis using interactive analysis models. The results of the study found that the Malang district government played a role in the development of panoramic farmer groups by providing counselling and training to members of farmer groups, this phenomenon indicates that the government and stakeholders have participated in carrying out their duties based on the provisions of Article 66 of Law Number 19 of 2013 concerning Protection and Empowerment Farmers, by facilitating farming capital, are proven to have legal protection for the Panoramic Farmer Group. They receive assistance from the government in the form of KUR loan assistance for agricultural operations with small interest and also receive assistance in the form of machinery, transportation equipment and building materials to support the quality of the Panorama Farmer Group's farmer production.